The meddlers sovereignty, empire, and the birth of global economic governance - Martin, Jamie, 1984- (Harvard University Press, 2022)
A pioneering history traces the origins of global economic governance--and the political conflicts it generates--to the aftermath of World War I. International economic institutions like the IMF and World Bank exert incredible influence over the domestic policies of many states. These institutions date from the end of World War II and amassed power during the neoliberal era of the late twentieth century. But as Jamie Martin shows, if we want to understand their deeper origins and the ideas and dynamics that shaped their controversial powers, we must turn back to the explosive political struggles that attended the birth of global economic governance in the early twentieth century. The Meddlers tells the story of the first international institutions to govern the world economy, including the League of Nations and Bank for International Settlements, created after World War I. These institutions endowed civil servants, bankers, and colonial authorities from Europe and the United States with extraordinary powers: to enforce austerity, coordinate the policies of independent central banks, oversee development programs, and regulate commodity prices. In a highly unequal world, they faced a new political challenge: was it possible to reach into sovereign states and empires to intervene in domestic economic policies without generating a backlash? Martin follows the intense political conflicts provoked by the earliest international efforts to govern capitalism--from Weimar Germany to the Balkans, Nationalist China to colonial Malaya, and the Chilean desert to Wall Street. The Meddlers shows how the fraught problems of sovereignty and democracy posed by institutions like the IMF are not unique to late twentieth-century globalization, but instead first emerged during an earlier period of imperial competition, world war, and economic crisis.